Urbanization beyond Municipal Boundaries: Nurturing Metropolitan Economies and Connecting Peri-Urban Areas in India - WorldBank (World Bank, 2015)
This study identifies three priority areas for India's policymakers as they try to harness economic efficiency and manage spatial equity associated with urbanization. First, to enhance productivity, invest in the institutional and information foundations to enable land and housing markets to function efficiently, while deregulating the intensity of land use in urban areas. This measure would require better coordination between planning for land use and planning for infrastructure, such that densification can be accompanied by infrastructure improvements. An incremental model of experimentation focusing on a few areas-say, around infrastructure corridors and neighborhoods-and then scaling up based on community-level consensus building can help in implementing densification reforms.